ELECTORAL IMMUNITY AND VOTE BUYING: REASSESSING ELECTION LAW ENFORCEMENT THROUGH THE PERSPECTIVE OF MASLAHAH MURSALAH - Vivi Rohmana; Siti Fatimah; Muhammad Adib Alfarisi (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2026)
Election law enforcement in Indonesia still faces a serious gap between the ideals of legal norms and the realities of practice on the ground. This gap is caused not only by a procedural and positivistic law enforcement paradigm, but also by the lack of synchronization between Law Number 7 of 2017 concerning General Elections and the technical provisions in the General Elections Commission Regulation (PKPU), as well as the weak implementation of election criminal norms in practice. Furthermore, the practice of money politics, dawn raids, and other transactional violations continues to recur and tends to end without effective criminal sanctions, thus perpetuating a culture of impunity and undermining electoral justice. This study aims to critically analyze the normative, structural, and philosophical factors that cause weak election law enforcement, as well as to reconstruct an election law enforcement model oriented towards substantive justice through the principle of maslahah mursalah. The research method used was normative juridical with a qualitative-philosophical approach through a review of primary legal materials, particularly Law Number 7 of 2017, as well as secondary legal materials and Islamic legal doctrine. The research findings indicated that the application of Articles 280 and 523 of the Election Law remains trapped in formalistic proof, thus failing to assess the socio-political impact of election violations. The principle of maslahah mursalah has proven philosophically and normatively relevant for interpreting and enforcing election law teleologically, emphasizing the protection of public interest and the prevention of democratic damage. Reconstructing election law enforcement based on maslahah mursalah has the potential to close the gap in impunity, strengthen legal legitimacy, and contribute to sustainable national stability. Abstrak Penegakan hukum pemilu di Indonesia masih menghadapi kesenjangan serius antara idealitas norma hukum dan realitas praktik di lapangan. Kesenjangan tersebut tidak hanya disebabkan oleh paradigma penegakan hukum yang prosedural dan positivistik, tetapi juga oleh ketidaksinkronan antara Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum dan pengaturan teknis dalam Peraturan Komisi Pemilihan Umum (PKPU), serta lemahnya implementasi norma pidana pemilu dalam praktik. Selain itu, praktik politik uang, serangan fajar, dan pelanggaran transaksional lainnya terus berulang dan cenderung berakhir tanpa sanksi pidana yang efektif, sehingga melanggengkan budaya imunitas dan merusak keadilan elektoral. Penelitian ini bertujuan menganalisis secara kritis faktor normatif, struktural, dan filosofis yang menyebabkan lemahnya penegakan hukum pemilu, serta merekonstruksi model penegakan hukum pemilu yang berorientasi pada keadilan substantif melalui prinsip maslahah mursalah. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan kualitatif-filosofis melalui telaah terhadap bahan hukum primer, khususnya Undang-Undang Nomor 7 Tahun 2017, serta bahan hukum sekunder dan doktrin hukum Islam. Hasil penelitian menunjukkan bahwa penerapan Pasal 280 dan Pasal 523 Undang-Undang Pemilu masih terjebak pada pembuktian formalistik, sehingga gagal menilai dampak sosial-politik pelanggaran pemilu. Prinsip maslahah mursalah terbukti relevan secara filosofis dan normatif untuk menafsirkan dan menegakkan hukum pemilu secara teleologis, dengan menekankan perlindungan kemaslahatan publik dan pencegahan kerusakan demokrasi. Rekonstruksi penegakan hukum pemilu berbasis maslahah mursalah berpotensi menutup celah imunitas, memperkuat legitimasi hukum, dan berkontribusi pada stabilitas nasional yang berkelanjutan.